Hepatoprotective and Antifibrotic Effects of Indonesian Propolis (Majalah Kedokteran Bandung, 2019)
Liver cirrhosis is the irreversible stage in liver damage process which occurs after liver fibrosis due to necro-inflammatory activities and liver fibrosis. Therefore, inhibition of liver inflammation and fibrosis is very important to prevent liver cirrhosis. This study aimed to analyze the effect of ethanol extract of propolis (EEP) from mount Lawu, Indonesia to prevent liver damage and fibrosis progression in mice with hepatic cirrhosis. This study was performed during the period of June 2018 to May 2019 on a sample of 32 male Balb/C mice divided into control group (P1), induction of carbon tetrachloride (CCl4 ) group (P2), induction of 50 mg/BW CCl4 + EEP group (P3), and (induction of 100 mg/KgBW CCl4 + EEP (P4) with each group consisted of eight mice. The CCl4 in olive oil was administered intraperitoneally three times a week for six weeks. Mean differences between group was determined using ANOVA test with a significance level of 0.05. The induction of CCl4 increased liver cell damage and serum alanin aminotransferase (ALT) level. However, the addition of EEP significantly (p
Keywords: ALT; APRI score; liver cirrhosis; liver damage; propolis